Dystrophic phenotype improvement in the diaphragm muscle of mdx mice by diacerhein. - Rafael Dias Mâncio; Túlio de Almeida Hermes; Aline Barbosa Macedo; Daniela Sayuri Mizobuti; Ian Feller Rupcic; Elaine Minatel (PLoS ONE)
Chronic inflammation and oxidative stress are striking features of Duchenne muscular dystrophy disease. Diacerhein is an anthraquinone, which exhibits anti-inflammatory and antioxidant properties. Based on their actions, the present study evaluated the effects of diacerhein against myonecrosis, oxidative stress and inflammatory response in the diaphragm muscle of mdx mice and compared these results to current treatment widely used in DMD patients, with a main focus on the impact of prednisone. The results demonstrated that diacerhein treatment prevented muscle damage indicated by a decrease in the IgG uptake by muscle fibers, lower CK levels in serum, reduction of fibers with central nuclei with a concomitant increase in fibers with peripheral nuclei. It also had an effect on the inflammatory process, decreasing the inflammatory area, macrophage staining and TNF-α and IL-1β content. Regarding oxidative stress, diacerhein treatment was effective in reducing the ROS and lipid peroxidation in the diaphragm muscle from mdx mice. Compared to prednisone treatment, our findings demonstrated that diacerhein treatment improved the dystrophic phenotype in the diaphragm muscle of mdx mice similar to that of glucocorticoid therapy. In this respect, this work suggests that diacerhein has a potential use as an alternative drug in dystrophinopathy treatment and recommends that its anti-inflammatory and antioxidants properties in the dystrophic muscle should be better understood.